Physically Cross-Linked PVA Hydrogels as Potential Wound Dressings: How Freezing Conditions and Formulation Composition Define Cryogel Structure and Performance - Anna Górska; Ewelina Baran; Justyna Knapik-Kowalczuk; Joanna Szafraniec-Szczęsny; Marian Paluch; Piotr Kulinowski; Aleksander Mendyk (MDPI AG, 2024)
Objectives: Hydrogels produced using the freeze-thaw method have demonstrated significant potential for wound management applications. However, their production requires precise control over critical factors including freezing temperature and the choice of matrix-forming excipients, for which no consensus on the optimal conditions currently exists. This study aimed to address this gap by evaluating the effects of the above-mentioned variables on cryogel performance. Methods: Mechanical properties, absorption capacity, and microstructure were assessed alongside advanced analyses using differential scanning calorimetry (DSC) and low-field nuclear magnetic resonance relaxometry (LF TD NMR). Results: The results demonstrated that fully hydrolyzed polyvinyl alcohol (PVA) with a molecular weight above 61,000 g/mol is essential for producing high-performance cryogels. Among the tested formulations, an 8% (w/w) PVA56-98 solution (Mw~195,000; DH = 98.0-98.8%) with 10% (w/w) propylene glycol (PG) provided the best balance of stretchability, durability, and low adhesion. Notably, while −25 °C is often used for cryogel preparation, freezing the gel precursor at −80 °C yielded superior results, producing materials with more open, interconnected structures and enhanced mechanical strength and elasticity-deviating from conventional practices. Conclusions: The designed cryogel prototypes exhibited functional properties comparable to or even surpassing commercial wound dressings, except for absorption capacity, which remained lower. Despite this, the cryogel prototypes demonstrated potential as wound dressings, particularly for use in dry or minimally exuding wounds. All in all, this study provides a comprehensive analysis of the physicochemical and functional properties of PVA cryogels, establishing a strong foundation for the development of advanced wound dressing systems.